2019
DOI: 10.1002/mbo3.907
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bacterial diversity and pathogen abundances in gibel carp (Carassius auratus gibelio) ponds during a cyprinid herpesvirus 2 outbreak

Abstract: Cyprinid herpesvirus 2 (CyHV‐2) infection is detrimental to gibel carp health and may result in severe economic loss in freshwater aquaculture. However, information regarding the interaction of this pathogen with the aquatic environment is scarce. In this study, quantitative polymerase chain reaction (qPCR) and high‐throughput sequencing were used to determine the abundances of pathogens and bacterial community compositions in two aquaculture ponds in Jiangsu Province, China. The results indicate that the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…abundance in pond water (Gao et al . 2019). In our study, alpha diversity indexes in the aquaculture ponds were lower than those in the source water, which can be attributed to the aquaculture operations.…”
Section: Resultsmentioning
confidence: 99%
“…abundance in pond water (Gao et al . 2019). In our study, alpha diversity indexes in the aquaculture ponds were lower than those in the source water, which can be attributed to the aquaculture operations.…”
Section: Resultsmentioning
confidence: 99%
“…CyHV-2 abundance is positively correlated with dissolved oxygen levels and the presence of abundant Aeromonas spp. in pond water [21]. Plant roots with stronger dissolved oxygen levels and biological nitrification inhibition capacities suppress the populations of Nitrospira in the rhizosphere, Comparisons were also performed to identify the microorganisms that can transform in different media at 30 d (water, roots, and sediment).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrospirae sig-nificantly increased and decreased in the HcT1 and Jr root groups, respectively, in the present study, with our previous study results showing that HcT1 and Jr are involved in nitrogen and phosphorus removal. The total phosphorus concentration in the pond sediment was the main reason for cyanobacterial blooms [23], with the Ruminococcaceae, Gemmatimonadetes [24], and Cyanobacteria (sediment) [21] populations increasing in the Jr group [25], with Jr releasing yellow allelochemicals, which may inhibit the growth of algae (like cyanobacterial blooms) [26] and nitrite-oxidizing bacteria (Nitrospirae) [27]; our previous study showed that Jr may have potent algae prevention effects in ponds [4]. However, the abundance of some anti-stress bacteria, such as Chlorobi and Fusobacterium, increased.…”
Section: Discussionmentioning
confidence: 99%